2021
DOI: 10.3389/fimmu.2021.775128
|View full text |Cite
|
Sign up to set email alerts
|

Leukemic Stem Cells: From Leukemic Niche Biology to Treatment Opportunities

Abstract: Acute myeloid leukemia (AML) is one of the most common types of leukemia in adults. While complete remission can be obtained with intensive chemotherapy in young and fit patients, relapse is frequent and prognosis remains poor. Leukemic cells are thought to arise from a pool of leukemic stem cells (LSCs) which sit at the top of the hierarchy. Since their discovery, more than 30 years ago, LSCs have been a topic of intense research and their identification paved the way for cancer stem cell research. LSCs are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 166 publications
1
27
0
Order By: Relevance
“…NF-κB plays a pivotal role also in LSCs, where it regulates survival, proliferation and chemoresistance [ 28 ]. Zhou and collaborators demonstrated that NF-κB fosters stem-like properties (i.e., self-renewal capacity) of AML cells via LIN28B activation.…”
Section: Nf-κb Pathway In Aml Pathogenesismentioning
confidence: 99%
“…NF-κB plays a pivotal role also in LSCs, where it regulates survival, proliferation and chemoresistance [ 28 ]. Zhou and collaborators demonstrated that NF-κB fosters stem-like properties (i.e., self-renewal capacity) of AML cells via LIN28B activation.…”
Section: Nf-κb Pathway In Aml Pathogenesismentioning
confidence: 99%
“…In this scenario, research diverges in different areas such as transport proteins and signaling pathways, taking as an example Notch, Hedgehog, and Wnt/b-catenin that are describes also as responsible for drug resistance (104,(127)(128)(129). It is also worth mentioning studies focused on the epithelial-mesenchymal transition (EMT), histone acetylation, hypoxia and the BM niche (104,130,131).…”
Section: Treatment Perspectivesmentioning
confidence: 99%
“…Leukemic stem cells (LSCs) are multipotent, proliferative, and self-renewing cells that propagate leukemia ( 210 ). In AML LSCs, oxysterol-binding protein-related protein 4L (ORP4L) acts as a scaffold protein that facilitates PIP2 presentation to PLC-β3 for cleavage into IP3 ( 211 ).…”
Section: Calcium Signaling Deregulation In Blood Cancermentioning
confidence: 99%